Implementasi Strategi Membaca dan Menghafal Al Qur’an dan Pengaruhnya Terhadap Kemampuan Membaca dan Menulis Arab permulaan - Achmad Pandu Setiawan (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
It was realized and became a consensus that education including Islamic education had a big contribution in realizing a superior civilization of the nation. But the fact states that the direction of Islamic education is still lagging behind and not to mention the dualism of the education system in Indonesia that is dictoomic (contradictory which tends to distance from one another) Based on the problem statement, this study aims to describe the Implementation Strategy of reading and memorizing the Qur'an and its influence on the ability to read and write Arabic beginning. This study follows an exploratory, descriptive and explanatory research design. The population is 23,960 children consisting of 279 Institutions (Al-Qur'an Education Park). The method of sampling in this study is that this study uses a simple random sampling system with the Slovin formula and from the members of the population taken as samples there are 100 respondents with the level of sig. p (0.01) In this study the authors used multiple linear regression analysis techniques. The results of this study concluded that there was a significant positive effect on the implementation of reading and memorizing strategies for the ability to read and write Arabic beginning